Question
upstudy study bank question image url

Exercice 1: (15.5 pts) \( (1+2+1) \) 1. Résoudre dans \( \mathbb{R} \) les équations et inéquation suivantes. - \( \frac{2 x-1}{2}+\frac{3 x-2}{4}=20-\frac{5 x}{7} \) - \( |2 x-6|+|x+6|=5 \) 2. Soit le polynome \( P(x)=2 x^{3}-5 x^{2}-x+6 \) (2) (2) (2.5) (2) \( (1+2) \) (a) Résoudre dans \( \mathbb{R} \) l'équation \( 2 x^{2}-7 x+6=0 \) (b) Calculer \( P(1) \) et \( P(-1) \) (c) En utilisant une division euclidienne, factoriser \( P(x) \) (d) Ecrire \( P(x) \) sous forme d'un produit de binomes (e) Résoudre \( P(x)=0 \) et \( P(x)>0 \)

Ask by Hammond Bowman. in Morocco
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

### Exercice 1: Résolution des Équations et Polynômes 1. **Résolution des Équations et Inéquations** **a. Équation :** \[ \frac{2x - 1}{2} + \frac{3x - 2}{4} = 20 - \frac{5x}{7} \] - **Solution :** \[ x = \frac{196}{23} \] **b. Équation :** \[ |2x - 6| + |x + 6| = 5 \] - **Solution :** Aucune solution dans \(\mathbb{R}\). **c. Équation :** \[ 2x^2 - 7x + 6 = 0 \] - **Solutions :** \[ x_1 = \frac{3}{2}, \quad x_2 = 2 \] 2. **Polynôme \( P(x) = 2x^3 - 5x^2 - x + 6 \)** **a. Calcul de \( P(1) \) :** \[ P(1) = 2(1)^3 - 5(1)^2 - 1 + 6 = 2 - 5 - 1 + 6 = 2 \] **b. Calcul de \( P(-1) \) :** \[ P(-1) = 2(-1)^3 - 5(-1)^2 - (-1) + 6 = -2 - 5 + 1 + 6 = 0 \] **c. Résolution de \( P(x) = 0 \) :** - **Solutions :** \[ x_1 = -1, \quad x_2 = \frac{3}{2}, \quad x_3 = 2 \] **d. Factorisation de \( P(x) \) :** En utilisant la division euclidienne, \( P(x) \) peut être écrit comme : \[ P(x) = (x + 1)(2x - 3)(x - 2) \] **e. Résolution de \( P(x) > 0 \) :** - **Intervalle où \( P(x) > 0 \) :** \[ x < -1 \quad \text{ou} \quad x > 2 \] ### Conclusion Nous avons résolu les équations et inéquations proposées, calculé les valeurs du polynôme en \( x = 1 \) et \( x = -1 \), et factorisé le polynôme \( P(x) \).

Solution

Evaluate the expression by following steps: - step0: Evaluate: \(2x^{3}-5x^{2}-x+6\) - step1: Substitute: \(2\times 1^{3}-5\times 1^{2}-1+6\) - step2: Evaluate the power: \(2\times 1-5\times 1^{2}-1+6\) - step3: Evaluate the power: \(2\times 1-5\times 1-1+6\) - step4: Multiply: \(2-5\times 1-1+6\) - step5: Multiply: \(2-5-1+6\) - step6: Calculate: \(2\) Solve the equation \( 2 x^{2}-7 x+6=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(2x^{2}-7x+6=0\) - step1: Factor the expression: \(\left(x-2\right)\left(2x-3\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&2x-3=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=\frac{3}{2}\end{align}\) - step4: Rewrite: \(x_{1}=\frac{3}{2},x_{2}=2\) Substitute \( x=-1 \) into the expression \( 2 x^{3}-5 x^{2}-x+6 \). Evaluate the expression by following steps: - step0: Evaluate: \(2x^{3}-5x^{2}-x+6\) - step1: Substitute: \(2\left(-1\right)^{3}-5\left(-1\right)^{2}-\left(-1\right)+6\) - step2: Evaluate the power: \(2\left(-1\right)^{3}-5\times 1-\left(-1\right)+6\) - step3: Multiply the terms: \(-2-5\times 1-\left(-1\right)+6\) - step4: Multiply: \(-2-5-\left(-1\right)+6\) - step5: Subtract the numbers: \(-7-\left(-1\right)+6\) - step6: Subtract the terms: \(-6+6\) - step7: Add the numbers: \(0\) Solve the equation \( \frac{2 x-1}{2}+\frac{3 x-2}{4}=20-\frac{5 x}{7} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{2x-1}{2}+\frac{3x-2}{4}=20-\frac{5x}{7}\) - step1: Multiply both sides of the equation by LCD: \(\left(\frac{2x-1}{2}+\frac{3x-2}{4}\right)\times 28=\left(20-\frac{5x}{7}\right)\times 28\) - step2: Simplify the equation: \(49x-28=560-20x\) - step3: Move the expression to the left side: \(49x+20x=560+28\) - step4: Add and subtract: \(69x=560+28\) - step5: Add and subtract: \(69x=588\) - step6: Divide both sides: \(\frac{69x}{69}=\frac{588}{69}\) - step7: Divide the numbers: \(x=\frac{196}{23}\) Solve the equation \( |2 x-6|+|x+6|=5 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\left|2x-6\right|+\left|x+6\right|=5\) - step1: Move the expression to the left side: \(\left|2x-6\right|+\left|x+6\right|-5=0\) - step2: Separate into possible cases: \(\begin{align}&2x-6+x+6-5=0,2x-6\geq 0,x+6\geq 0\\&2x-6-\left(x+6\right)-5=0,2x-6\geq 0,x+6<0\\&-\left(2x-6\right)+x+6-5=0,2x-6<0,x+6\geq 0\\&-\left(2x-6\right)-\left(x+6\right)-5=0,2x-6<0,x+6<0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=\frac{5}{3},x\geq 3,x\geq -6\\&x=17,x\geq 3,x<-6\\&x=7,x<3,x\geq -6\\&x=-\frac{5}{3},x<3,x<-6\end{align}\) - step4: Find the intersection: \(\begin{align}&x \in \varnothing \\&x \in \varnothing \\&x \in \varnothing \\&x \in \varnothing \end{align}\) - step5: Find the union: \(x \in \varnothing \) Solve the equation \( 2 x^{3}-5 x^{2}-x+6=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2x^{3}-5x^{2}-x+6=0\) - step1: Factor the expression: \(\left(x-2\right)\left(x+1\right)\left(2x-3\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&x+1=0\\&2x-3=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=-1\\&x=\frac{3}{2}\end{align}\) - step4: Rewrite: \(x_{1}=-1,x_{2}=\frac{3}{2},x_{3}=2\) Expand the expression \( 2 x^{3}-5 x^{2}-x+6 \) Simplify the expression by following steps: - step0: : \(2x^{3}-5x^{2}-x+6\) Solve the equation \( P(x)>0 \). Solve the inequality by following steps: - step0: Solve for \(P,x\): \(Px>0\) - step1: Separate into possible cases: \(\begin{align}&\left\{ \begin{array}{l}P>0\\x>0\end{array}\right.\\&\left\{ \begin{array}{l}P<0\\x<0\end{array}\right.\end{align}\) - step2: Find the union: \(\begin{align}&\left\{ \begin{array}{l}P<0\\x<0\end{array}\right.\\&\left\{ \begin{array}{l}P>0\\x>0\end{array}\right.\end{align}\) ### Exercice 1: Résolution des équations et polynômes #### 1. Résoudre les équations et inéquations **a. Équation :** \[ \frac{2 x-1}{2}+\frac{3 x-2}{4}=20-\frac{5 x}{7} \] **Solution :** En résolvant cette équation, nous trouvons : \[ x = \frac{196}{23} \] --- **b. Équation :** \[ |2 x-6|+|x+6|=5 \] **Solution :** Cette équation n'a pas de solution dans \(\mathbb{R}\) : \[ x \in \varnothing \] --- **c. Équation :** \[ 2 x^{2}-7 x+6=0 \] **Solution :** Les solutions de cette équation sont : \[ x_{1} = \frac{3}{2}, \quad x_{2} = 2 \] --- #### 2. Polynôme \( P(x) = 2 x^{3}-5 x^{2}-x+6 \) **a. Calculer \( P(1) \) :** \[ P(1) = 2(1)^{3} - 5(1)^{2} - (1) + 6 = 2 - 5 - 1 + 6 = 2 \] **b. Calculer \( P(-1) \) :** \[ P(-1) = 2(-1)^{3} - 5(-1)^{2} - (-1) + 6 = -2 - 5 + 1 + 6 = 0 \] **c. Résoudre \( P(x) = 0 \) :** Les solutions de l'équation \( P(x) = 0 \) sont : \[ x_{1} = -1, \quad x_{2} = \frac{3}{2}, \quad x_{3} = 2 \] **d. Factoriser \( P(x) \) :** En utilisant la division euclidienne, nous pouvons écrire \( P(x) \) sous forme de produit de binômes. **e. Résoudre \( P(x) > 0 \) :** Les intervalles où \( P(x) > 0 \) sont : \[ \left\{ P < 0; x < 0 \right\}; \quad \left\{ P > 0; x > 0 \right\} \] ### Conclusion Nous avons résolu les équations et inéquations demandées, calculé les valeurs du polynôme en \( x = 1 \) et \( x = -1 \), et factorisé le polynôme \( P(x) \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Pour la première équation \( \frac{2 x-1}{2}+\frac{3 x-2}{4}=20-\frac{5 x}{7} \), multiplions chaque terme par 28 (le plus petit commun multiple) pour éliminer les dénominateurs. Cela nous donne \( 28 \cdot \left(\frac{2x-1}{2}\right) + 28 \cdot \left(\frac{3x-2}{4}\right) = 28 \cdot 20 - 28 \cdot \left(\frac{5x}{7}\right) \). Résolvons cette équation. Pour l’inéquation \( |2 x-6|+|x+6|=5 \), nous devons considérer les différents cas basés sur les valeurs où les expressions à l'intérieur des valeurs absolues changent de signe. Cela nous conduira à plusieurs sous-cas à résoudre. En ce qui concerne le polynôme \( P(x)=2 x^{3}-5 x^{2}-x+6 \), commençons par résoudre l'équation quadratique \( 2 x^{2}-7 x+6=0 \) en utilisant la formule quadratique. Cela nous donnera les racines du polynôme. Pour \( P(1) \) et \( P(-1) \), il suffit de substituer \( x=1 \) et \( x=-1 \) dans le polynôme pour calculer les valeurs correspondantes. Utilisons ensuite la division euclidienne pour factoriser \( P(x) \), ce qui nous permet de réécrire \( P(x) \) sous forme de produit de binômes. Enfin, trouvons \( P(x)=0 \) et \( P(x)>0 \) en examinant les racines et le signe du polynôme à l'aide de l’étude de signe sur les intervalles déterminés par ses racines.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy